Effect of comprehensive nutrition management on blood glucose and pregnancy outcome of individuals with gestational diabetes mellitus - WANG Rui, QI Mingming, YANG Weitao, HUANG Jian, XIAO Jinyan, LI Yichun, WANG Yonghong, LIU Yanping (Jichu yixue yu linchuang, 2024)
Objective To investigate the effects of comprehensive nutrition management on glycolipid metabolism and pregnancy outcomes in patients with gestational diabetes mellitus(GDM). Methods A total of 121 pregnant women with GDM at 24-28 weeks gestation who were registered in the obstetrics department of 6 sub-central hospitals in China from May 2021 to July 2021 were included in this study and were randomly divided into intervention group(n=74) and control group(n=47). The intervention group received intensive comprehensive nutrition management, including at least 6 outpatient interventions, individualized nutrition management and a half-day standardized outpatient education on gestational diabetes mellitus, continuous dynamic blood glucose monitoring and micro-blood glucose monitoring,and routine check of glycated albumin and urine every 4 weeks. Body weight, body composition and diet and exercise implementation procedures and fetal development as well as complications were recorded. The control group received conventional nutritional guidance. The two groups were compared for difference in blood glucose related indicators at 37 weeks of gestation, weight gain before delivery, some lipid metabolism indicators, pregnancy outcomes, and oral glucose tolerance test(OGTT) at 42 days postpartum. Results Compared with the control group, the level of prenatal fasting blood glucose(P=0.006), intravenous plasma glucose(P=0.009) and blood ketone(P=0.044) in the intervention group was significantly reduced. There was no significant difference in weight gain and weight attainment rate between the two groups. The 2-hour postpartum OGTTs of pregnant women in the intervention group(P=0.006) were significantly lower than those in the control group, and the incidence of preeclampsia and postpartum blood loss were lower than those in the control group but no statistical difference was found. For newborns, the incidence of macrosomia(P=0.042) and planation(P=0.048) in the intervention group was slightly lower than that in the control group, and the results were statistically different. Other adverse pregnancy outcomes were not statistically different between the two groups. Conclusions Intensive comprehensive nutrition management has a positive impact on the control of the blood glucose in pregnant women and improves the maternal and neonatal outcomes of women with GDM.